Screening for Methicillin-resistant Staphylococcus aureus Carriage on the Hands of Healthcare Workers: An Assessment for Hand Hygiene Practices - Sharma, Anuradha (Indian J Crit Care Med, 2019)
BACKGROUND: Methicillin-resistant Staphylococcus aureus (MRSA) is capable of causing a wide range of infections. Colonized healthcare workers (HCWs) and contaminated hand-touch surfaces act as a potential source of MRSA in hospitals. This study was conducted to detect the carriage of MRSA in the hands of HCWs during patient care to check awareness among HCWs to follow proper hand hygiene protocol. MATERIALS AND METHODS: This study was a cross-sectional point prevalence study done in wards and intensive care units (ICUs) of a tertiary care hospital. Hand cultures were collected from HCWs after the clinical rounds, without prior information about the procedure. It was done on three consecutive days to include maximum HCWs from the hospital. Cultures were taken before and after the use of alcohol-based hand rub. Hand cultures were obtained by asking HCWs to touch the surface of chromogenic screening agar for MRSA with their fingertips and thumbs of both the hands. RESULTS: Of a total of 62 HCWs screened, 32 (51.61%) were positive for MRSA. Among these, seven were doctors. After using alcohol-based hand rub, six HCWs were still positive for MRSA. Another important finding on this screening agar was detection of Candida on the hands of HCWs. CONCLUSION: Regular monitoring of hand hygiene compliance is vital to prevent the spread of nosocomial infections. The MRSA screening agar is rapid, simple, cost-effective, and useful to identify the carriage of not only MRSA but also Candida (in the wake of nosocomial outbreaks with Candida auris) in the hands of HCWs. Further studies are required to evaluate the transmission rate of MRSA from HCWs to patients in Indian hospitals. HOW TO CITE THIS ARTICLE: Sharma A, Kalita JM, Nag VL. Screening for Methicillin-resistant Staphylococcus aureus Carriage on the Hands of Healthcare Workers: An Assessment for Hand Hygiene Practices. Indian J Crit Care Med 2019;23(12):590–592.